Changes in Organic, Inorganic contents, Carbon Nitrogen ratio in decomposingAvicennia marinaand Rhizophora mucronataleaves on tidal mudflats in Hajambro creek, Indus delta, Pakistan - Farooqui, Zafar; Siddiqui, Pirzada Jamal; Rasheed, Munawwer (Journal of Tropical Life Science, 2014)
Leaf decomposition of Avicennia marina (ForskÃ¥l) Vierh in Denkschr and Rhizophora mucronata (Poiret) was studied in situ using litterbags in Hajambro creek, Indus deltA. A single exponential model was presented, which best described the rate of decomposition for both the species. The rate of decomposition was species specific, A. marina leaves decomposed slower than the R. mucronata (p